Локалізація полімерного ланцюжка поблизу двох проникних поверхонь поділу в постійному магнітному полі - Gerasimchuk, I.V.; Gerasimchuk, V.S.; Gorobets, Yu.I.; Sommer, J.-U. (Publishing house "Academperiodika", 2022)
We investigate the polymer chain localization in the system of two penetrable interfaces in an external constant magnetic field within the mean-field approximation. The saturation of a polymer chain in the limiting case of zero bulk concentration is studied. We obtain a non-monotonous behavior of the amount of adsorbed polymers as a function of the distance between the interfaces.